2000
DOI: 10.1177/107110070002100902
|View full text |Cite
|
Sign up to set email alerts
|

Subtalar Arthrodesis with Flexor Digitorum Longus Transfer and Spring Ligament Repair for Treatment of Posterior Tibial Tendon Insufficiency

Abstract: The surgical treatment of flexible pes planovalgus deformities resulting from Stage 2 posterior tibial tendon insufficiency is controversial and many techniques have been proposed. We retrospectively reviewed the results of subtalar arthrodesis combined with spring ligament repair/reefing and flexor digitorum longus (FDL) transfer to the navicular. There were sixteen patients (seventeen feet) with an average follow-up of 27 months (9-52). All deformities were passively correctable. The average age was 56 yrs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…There is support in the literature for the use of isolated subtalar arthrodesis to treat acquired adult flatfoot deformity when the patient has a fixed deformity of the subtalar joint and a flexible forefoot 22,23 . Mann et al stated that 10° to 15° of forefoot varus or joint hypermobility is a contraindication to isolated subtalar joint fusion 10 .…”
Section: Isolated Subtalar Arthrodesis With Flexor Digitorum Longus Tmentioning
confidence: 99%
See 3 more Smart Citations
“…There is support in the literature for the use of isolated subtalar arthrodesis to treat acquired adult flatfoot deformity when the patient has a fixed deformity of the subtalar joint and a flexible forefoot 22,23 . Mann et al stated that 10° to 15° of forefoot varus or joint hypermobility is a contraindication to isolated subtalar joint fusion 10 .…”
Section: Isolated Subtalar Arthrodesis With Flexor Digitorum Longus Tmentioning
confidence: 99%
“…Johnson et al reported on seventeen feet treated with subtalar joint arthrodesis, reconstruction of the flexor digitorum longus, and repair of the spring ligament 22 . At two years postoperatively, the results compared favorably with those of medial displacement calcaneal osteotomy and lateral column lengthening.…”
Section: Outcomes and Complicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be important when a longer part of tendon is required, such as in procedures for posterior tibial tendon insufficiency where the FHL tendon has to be pulled through a drill-hole in the navicular tuberosity. 6 In the literature covering FHL tendon transfer, little attention has been given to the difficulties that arise while harvesting the FHL tendon. However, when a double-incision technique is used and transection is made distal to the knot of Henry, we observed difficulties in harvesting the FHL tendon because of cross-attachments between FHL and FDL, which required a more extensive dissection.…”
Section: Introductionmentioning
confidence: 99%